Screening for carbohydrate-binding proteins in extracts of Uruguayan plants - Plá,A. (2003)
The presence of carbohydrate-binding proteins, namely lectins, ß-galactosidases and amylases, was determined in aqueous extracts of plants collected in Uruguay. Twenty-six extracts were prepared from 15 Uruguayan plants belonging to 12 Phanerogam families. Among them, 18 extracts caused hemagglutination (HAG) that was inhibited by mono- and disaccharides in 13 cases, indicating the presence of lectins. The other 8 extracts did not cause any HAG with the four systems used to detect HAG activity (rabbit and mouse red cells, trypsin-treated rabbit and mouse red cells). For the extracts prepared from Solanum commersonii, HAG activity and HAG inhibition were similar for those prepared from tubers, leaves and fruits, with the chitocompounds being responsible for all the inhibitions. Purification of the S. commersonii tuber lectin was carried out by affinity chromatography on asialofetuin-Sepharose, and SDS-PAGE under reducing conditions gave a single band of Mr of approximately 80 kDa. The monomer N-acetylglucosamine did not inhibit HAG induced by the purified lectin, but chitobiose inhibited HAG at 24 mM and chitotriose inhibited it at 1 mM. ß-Galactosidase activity was detected in leaves and stems of Cayaponia martiana, and in seeds from Datura ferox. Only traces of amylase activity were detected in some of the extracts analyzed. The present screening increases knowledge about the occurrence of carbohydrate-binding proteins present in regional plants.